PENGARUH PREDIKSI KEBAGKRUTAN MODEL ALTMAN Z-SCORE DAN ZMIJEWSKI X-SCORE TERHADAP HARGA SAHAM - Eti Muliati; Nafisah Nurulrahmatia; Alwi (Jurnal Kajian Akuntansi dan Auditing, 2024)
Every company has the goal of continuing to carry out its operational activities well, so that it can survive and optimize its profits. However, there are several companies that experience problems that cause operational activities to be hampered, resulting in a continuous decline in profits or losses, which ultimately results in them being threatened with bankruptcy. This research aims to determine the influence of the Altman Z-Score and Zmijewski X-Score bankruptcy prediction models on stock prices. The samples used in this research were transportation subsector companies listed on the Indonesia Stock Exchange from 2018-2022, with the number of samples used being 6 companies obtained using purposive sampling techniques. The data analysis techniques used are the classical assumption test, multiple linear regression test, correlation coefficient and determination coefficient test, t test and f test. The research results show that the Altman Z-Score model's bankruptcy prediction has a partially significant influence on stock prices. The Zmijewski X-score model has a partially significant influence on stock prices. There is a significant influence simultaneously on the prediction of failure of the Altman Z-Score and Zmijewski X-Score models on the share prices of transportation subsector companies listed on the Indonesia Stock Exchange.